The willful princess and the piebald prince - Hobb, Robin (Subterranean Press, 2013)
Felicity, a minstrel sworn to the truth, tells the ill-fated love story of the stubborn and indulged Princess Caution and the stableboy Lostler, a former Chalcedean slave and the piebald horse bound to him by the magic of Wit, which gives him the power to communicate with animals.